Optimisation of Live Streaming Process in the Post Covid-19 World (Proceeding of the International Conference on Arts and Humanities, 2021)
This study documents a relative improvement on sound quality by selected power-users to stream a music performance through a live streaming platform using an improved method. To gather necessary information, a survey was circulated, inquiring users’ perceptions and experiences regarding the common steps and methods, the use of third-party programme and difficulties of creating the live stream setup for live performance. Results of the survey determined which aspects of live streaming principles were emphasised in the control test, making any potential improvements upon streaming method of interest to those who took the survey. A control test was formulated, emphasizing the common live streaming methods and technical difficulties encountered by the participants. The control test was taken by five power-users from Malaysia which include a producer, a sound engineer, two freelance musicians and an educator. The resulting data was used as a new basis for improvement in the live streaming processes. Once the control test data was obtained, the next step was to analyse the processes in use and devise more efficient methods of executing them. As the aim of the research is to determine whether an increase in audio or sound quality could be made, a more detailed analysis of a small control group provided the information required to base improvements upon. For a qualitative study of this scope, survey and control testing were identified as being suitable collection methods.
Keywords: Performance; Live Stream; Methods; Optimisation